Monitoring the health of the greater Mekong’s rivers - Dickens, Chris; Cox, Amy; Johnston, Robyn M.; Davison, Supatra; Henderson, Derin; Meynell, Peter-John; Shinde, Victor R. (CGIAR Research Program on Water, Land and Ecosystems, 2018)
The methods used for biomonitoring can be sophisticated, producing highly accurate results, but can also be simplified for communities to use. In countries where budgets for biomonitoring are low, using community-based biomonitoring systems can effectively and cheaply tell us about a river’s health.